Literature study of building verticality monitoring analysis using GNSS and triaxial tiltmeter data integration - Gunawan, Aditya Z. M.; Saptari, Asep Y.; Suhandri, Hendy F.; Nasradeen A. Khalifa; Khairul Nizam Mohd Yunus (Penerbit Universiti Kebangsaan Malaysia, 2021)
The vertical housing system is a solution for the urban population which continues to increase as time goes. By using high-rise buildings, the land used for housing will be more effective. However, high-rise buildings have their own problems, one of which is bending due to the load acting on the building. One of the loads that causes bending in buildings is wind load. Bending will cause a major problem for the building’s endurance if the deviation exceeds the structural strength tolerance of the building, which will cause structural failure in the future. Therefore, it is necessary to periodically monitor the verticality of the building to detect this bending, both during and after constructions, to evaluate the performance and health of the building. The monitoring can be carried out using a variety of methods and equipment, one of which is particularly using the GNSS observation and triaxial tiltmeter measurement. GNSS measurement is used to detect the lateral displacement of the building, while the triaxial tiltmeter measurement is used to detect the deflection angle that is formed when the building is bending. To examine whether monitoring with GNSS and triaxial tiltmeter measurements can be used for practical purpose, this contribution delivers a simulation of wind load calculations to one high rise building in Bandung, Indonesia. This factor, in particular, is chosen to see the impact of bending on a building at high level floors. The wind load calculation refers to an Indonesian National Standard (SNI) 03-1727-2013, while the bending calculation will be carried out based on the beam deflection theory. Based on the simulation, it is found that the deflection that occurs at the highest level reaches 2.832 cm, and the largest deflection angle reaches 1.792”. Hypothetically, it can be stated that these values can be detected by the survey standard GNSS observation and the triaxial tiltmeter measurement since the accuracy of those two monitoring tools is smaller than the simulation results. In turn, the health and safety of the buildings being monitored can be determined, which leads to issuing of the building functionality certificate for the building insurance purpose.